2018
DOI: 10.1101/367516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel mutations associated with autosomal dominant congenital cataract are identified in Chinese families

Abstract: PurposeAs the leading cause of the impairment of vision of children, congenital cataract is considered as a hereditary disease, especially autosomal dominant congenital cataract (ADCC). The purpose of this study is to identify the genetic defect of six Chinese families with ADCC. Subjects and MethodsSix Chinese families with ADCC were recruited in the study. (103 members in total, 96 members alive, 27 patients in total) Genomic DNA samples extracting from probands' peripheral blood cells were captured the muta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This information indicates that the coralliform phenotype and the CRYGD gene are closely related. Our results support the idea that virulence genes and lens morphology are related 23 24 25 26 27 28 29 . Results of biophysical analysis have shown that the P24T mutant protein has a significantly lower solubility than wild-type human γD crystalline 30 31 .…”
Section: Discussionsupporting
confidence: 88%
“…This information indicates that the coralliform phenotype and the CRYGD gene are closely related. Our results support the idea that virulence genes and lens morphology are related 23 24 25 26 27 28 29 . Results of biophysical analysis have shown that the P24T mutant protein has a significantly lower solubility than wild-type human γD crystalline 30 31 .…”
Section: Discussionsupporting
confidence: 88%
“…Among them, BFSP2 (phakinin or CP49) and BFSP1 ( lensin) assemble into lens-speci c beaded intermediate laments, which are one of the main cytoskeletal structures in the lens ber [38,39] . BFSP1 and BFSP2 have been con rmed to be genes associated with autosomal dominant cataracts [40,41] . Moreover, the absence of BFSP2 or BFSP1 causes the disappearance of beaded intermediate laments and changes the morphology of lens ber cells [42] .…”
Section: Discussionmentioning
confidence: 99%
“…In current study, a wide spectrum cataract gene panel screening was performed in two probands from two separate Chinese congenital cataract pedigrees with autosomal dominant inheritance, a heterozygous variant of CRYGD gene in exon 2 (70C>A, P24T) was identified as a disease-causing gene as this mutation was co-segregated with the disease within two families. Previous studies reported that ten mutated variants in CRYGD gene, including P24T, and others such as R15S, R15C, P24S, R37S, R59H, G61C, and Y134X [18][19][20] , manifested with vast phenotypic variations as a result of genotypic heterogeneity [18,[21][22][23][24][25][26][27][28][29] . As examples, Y56X, Y134C, and R58H were reported to be related with nuclear cataract, lamellar cataract and aculeiform/coral-like cataract, respectively [22,[30][31] .…”
Section: Clinical Evaluationmentioning
confidence: 99%